2021
DOI: 10.1055/s-0041-1724093
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Calcium and Vitamin D with Benign Paroxysmal Positional Vertigo

Abstract: Introduction Benign paroxysmal positional vertigo (BPPV) is one of the common disorders of the peripheral vestibular system. The prevalence of BPPV is found to be higher among middle-aged women. Objectives To estimate the serum levels of calcium and vitamin D in patients with BPPV, and to study their association. Methods The present is a hospital-based prospective case-control study. Venous blood samples of the 49 patients with BPPV and an equal number of age- and gender-matched individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Bazoni et al, on the other hand, found no association between 25(OH) vitamin D levels and BPPV in the general population, but noted an association with bone mineral density in the elderly group with diabetes mellitus and BPPV [ 22 ]. While some research findings suggested no association between vitamin D levels and serum calcium in BPPV, a negative correlation was identified between vitamin D concentrations and the frequency of BPPV episodes ( p < 0.012) [ 23 ]. Several studies consistently reported low vitamin D status in patients with BPPV, with no significant differences in 25(OH)D levels between BPPV patients and controls [ 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bazoni et al, on the other hand, found no association between 25(OH) vitamin D levels and BPPV in the general population, but noted an association with bone mineral density in the elderly group with diabetes mellitus and BPPV [ 22 ]. While some research findings suggested no association between vitamin D levels and serum calcium in BPPV, a negative correlation was identified between vitamin D concentrations and the frequency of BPPV episodes ( p < 0.012) [ 23 ]. Several studies consistently reported low vitamin D status in patients with BPPV, with no significant differences in 25(OH)D levels between BPPV patients and controls [ 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Croatia reported that low vitamin D3 serum level is not a risk factor for BPPV recurrence [10]. Another study from India concluded that there is no association between calcium and vitamin D concentrations and BPPV [24]. A recent investigation from the United States found that BPPV patients had a significantly higher vitamin D level than the NHANES (National Health and Nutrition Examination Survey) individuals (31.4 ±16.5 vs. 26.0 ±11.2 ng/mL, d = 0.474 (0.323, 0.626)) [16].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies reported that compared with controls, patients with BPPV have lower average serum vitamin D levels 1 26–35. Seven studies found no significant difference between the serum vitamin D levels of BPPV patients and controls 36–42. Among cases and controls with osteoporosis and osteopenia, two studies2 43 found no significant difference between cases and controls, although osteoporosis was correlated with low serum vitamin D in BPPV patients 2.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The relationship between BPPV recurrence and serum 25-hydroxyvitamin D was examined in 12 studies, with 9 studies reporting lower serum vitamin D levels in patients with recurrent BPPV compared with those experiencing an initial attack1 31 35–37 42 45 46 and 3 reporting no significant difference in vitamin D levels between the 2 groups 38 47 48. Three studies41 49 50 reported that vitamin D supplementation reduced the number of recurrent episodes of BPPV.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation